(untitled) (Research, Society and Development, 2020)
The nursing home context, is a reality experienced by many elderlies in our country, thus has been thought about discussing health and psychic well-being issues within this panorama, as well as the process of subjectivation and lack of the very same. That being so, through this article the aim was to use music to recover some of the subjective of the elderly that in a certain way get lost within this type of institution because of the rules, norms and routines established. This study was conducted through bibliography research of qualitative approach, associated with the experience report that arose through an intervention proposal developed in a discipline taught in a graduation course in psychology of a university in the interior of Rio Grande do Sul and performed between October and November 2019. Was provided for the elderlies an environment which escaped from the everyday that oftentimes they are exposed, so they could dance, socialize with their colleagues and have fun. What was perceived is that the music caused a comfort, that they could remember experiences and the music awoke feelings and emotions of moments that they had belonged and that nobody can take of them. It is concluded that accentuating the importance of music not just for who get elder, but too in all the others ages. Besides that, it is worth mentioning the countless benefits to psychical and physical health that went proved in just one afternoon with music inside a nursing home institution.